Fragments and fragmentary vision in nineteenth-century architectural photographs. Issue 1 (2nd January 2021) - Sealy, Peter
Abstract: The frequent absence of views of buildings as unified, whole objects in nineteenth-century French architectural photography is striking, especially in publications for a professional audience. Instead, photographic views of contemporary architecture often focused upon two fragmentary forms: the ornamental detail (commonly represented through the intermediary of a plaster cast) and the spatial view, depicting an isolated "crop" extracted from a building. The former continues an archaeological tradition, linking historic restoration and historicist production through an indexical chain from cast to photograph. Images such as those in Édouard Baldus's Palais du Louvre (1869–75), Charles Garnier's Le Nouvel Opéra de Paris (1875–81), and Anatole de Baudot's Sculpture française (1884) freeze the subjective labor involved in ornamental design, disseminating it alternately for commercial reproduction or as motifs to inspire a living decorative tradition. Around 1870 another form of photographic fragmentation took hold, this time willfully dissolving the unity of the architectural object to focus upon moments of heightened visual interest. Motivated by a rising interest in spatiality, these "photo-scopic" images in the Gazette des architectes, Revue générale, Félix Narjoux's Monuments élevés (1880–83), and other publications instantiate a dynamic conception of architecture, one now open to subjective and atmospheric perception. While the ornamental fragment was often intended for recombination in future eclectic tableaux, the later morceaux demonstrate a new, modern form of vision, one that would greatly influence architecture in the twentieth century.